"Wiring" Fe‐Nx‐Embedded Porous Carbon Framework onto 1D Nanotubes for Efficient Oxygen Reduction Reaction in Alkaline and Acidic Media. Issue 26 (24th April 2017) - Ahn, Sung Hoon; Yu, Xingwen; Manthiram, Arumugam
Abstract : This study presents a novel metal‐organic‐framework‐engaged synthesis route based on porous tellurium nanotubes as a sacrificial template for hierarchically porous 1D carbon nanotubes. Furthermore, an ultrathin Fe‐ion‐containing polydopamine layer has been introduced to generate highly effective FeN x C active sites into the carbon framework and to induce a high degree of graphitization. The synergistic effects between the hierarchically porous 1D carbon structure and the embedded FeN x C active sites in the carbon framework manifest in superior catalytic activity toward oxygen reduction reaction (ORR) compared to Pt/C catalyst in both alkaline and acidic media. A rechargeable zinc‐air battery assembled in a decoupled configuration with the nonprecious pCNT@Fe@GL/CNF ORR electrode and Ni‐Fe LDH/NiF oxygen evolution reaction (OER) electrode exhibits charge–discharge overpotentials similar to the counterparts of Pt/C ORR electrode and IrO2 OER electrode. Abstract : Fe‐ and N‐co‐doped porous 1D carbon nanotubes protected by ultrathin graphitic layers exhibit remarkable electrocatalytic activity toward the oxygen reduction reaction (ORR) along with excellent long‐term stability in both alkaline and acidic media. Rechargeable zinc–air batteries based on these nonprecious catalysts in a decoupled configuration exhibit high round‐trip efficiency and excellent cyclic stability.